Improving clonal propagation of Eucalyptus grandis x urophylla with indole-3-butyric acid - Casas Niño, Sebastián (2026)
The Eucalyptus grandis × E. urophylla hybrid is characterized by its rapid growth and high productivity, which has led to an increasing demand for its propagation in nurseries. To preserve these desirable traits, it is essential to establish clonal gardens and apply effective clonal propagation methods. With the aim of advancing knowledge on asexual propagation techniques, this study evaluates the influence of indole-3-butyric acid (IBA) and a commercial formulation combining IBA and naphthaleneacetic acid (NAA) on the rooting and root development of cuttings of this hybrid. To achieve this, cuttings were collected from a clonal garden and subjected to five rooting treatments: T0 (control) with 0 ppm IBA; T1 with 1,000 ppm IBA; T2 with 1,500 ppm IBA; T3 with 2,000 ppm IBA; and T4, a commercial formulation containing 4,000 ppm NAA and 1,000 ppm IBA. The experiment was conducted under a completely randomized design (CRD) with 90 experimental units. After treatment application, the cuttings were placed in a greenhouse for 30 days. At the end of this period, rooting percentage, mortality rate, number of roots, root length, and root dry weight were assessed. The results indicated that T2 and T4 exhibited the best performance in terms of rooting and root development. Furthermore, comparison with other studies revealed that excessively high concentrations of IBA can exert toxic effects on cuttings. Overall, the study concludes that IBA, either alone or in combination with NAA, positively influences the rhizogenesis process of Eucalyptus grandis × E. urophylla cuttings, increasing rooting percentage by up to 62% compared to the control.